Pengaruh Laju Alir Udara Terhadap Produktifitas Syngas Gasifikasi Biomassa Kulit Kopi - Wiyono, Pandu Akbar Iqrofasya Wiyono; Stujanjono, Hary; Sidartawan, Robertus; Listiyadi, Digdo; Rozy, M. Fahrur; Sanata, Andi; Sholahuddin, Imam; Nashrullah, M. Dimyati (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2025)
Indonesia's natural resources, such as coffee hulls in Jember Regency, are potential sources of biomass raw materials that can be processed into biomass energy. Gasification is the process of converting solid fuels into combustible gases (CO, CH4, H2) through a heating process with minimal air conditions. This research focuses on the effect of air flow rate on the syngas productivity of coffee husk biomass gasification. It was found that higher air flow rate produces higher syngas content. The highest syngas composition with the highest LHV value was obtained by the 40 SCFH air flow rate variation with an LHV value of 141.7 kJ/mol.